Geo-Risk 2023 : Advances in Modeling Uncertainty and Variability. - Ching, Jianye (Geotechnical Special Publications, 2023)
GSP 347 contains 39 peer-reviewed papers on advances in modeling uncertainty and variability in geotechnical engineering presented at Geo-Risk 2023, held in Arlington, Virginia, July 23-26, 2023.